Ezrin Regulating the Cytoskeleton Remodeling is Required for Hypoxia-Induced Myofibroblast Proliferation and Migration - Yi, Bin; Chen, Lin; Zeng, Jing; Cui, Jian; Wang, Guansong; Qian, Guisheng; Belguise, Karine; Wang, Xiaobo; Lu, Kaizhi (Frontiers in Cardiovascular Medicine, 2015)
Background: Hypoxia pulmonary arterial hypertension (HPAH) is a disease of the small vessels characterized by sustained vasoconstriction, thickening of arterial walls, vascular remodelling, and progressive increase in pulmonary vascular resistance, thus leading to right heart failure and finally death. Recent evidence demonstrated that massive Pulmonary Artery Smooth Muscle-like Cells (PASMLCs) accumulating in the intima might also be developed from the differentiation of Pulmonary Myofibroblast (PMF) of tunica media. And PMF appeared the phenomenon of the cytoskeleton remodeling. So, it would be important in the clarification of the pivotal factors controlling this cytoskeleton structure change. Methods: PMFs were cultured from the normal rats and then divided into three groups and incubated by nomal or hypoxic conditions respectively. mRNA level was evaluated by real time reverse transcription polymerase chain reaction, and protein expression was detected by western blot. Cell proliferation was determined by the MTT and thymidine incorporation assay. Results: Here, we report that the hypoxia increased the expression levels of Ezrin mRNA and protein in PMFs, which might explain the expression of cytoskeletal proteins (Destrin, a1-actin, and a1-tubulin) in PMFs was significantly induced by hypoxia. After inhibiting Ezrin in PMFs by siRNA transfection, we found the over-expression of cytoskeletal proteins induced by hypoixa were significantly suppressed at all time points. Additionally, we found that hypoxia or over-expression of Ezrin through Ad-Ezrin transfection significantly increases the proliferation and migration of PMFs, and which could be inverted by the transfection of siRNA. Conclusion: These findings suggest that Ezrin regulating of aberrant dysregulation of cytoskeletal proteins may be the major cause of PMFs' proliferation and migration under the condition of hypoxia and may, therefore, play a fundamental role in the accumulation of PASMLCs of HPAH.